Pengembangan Pasar Digital pada UMKM Desa Batu Kumbang - Widyawati, Lilik; Melati Rosanensi; Hasbullah; Tomi Tri Sujaka; Christofer Satria (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
This time the community service for Bumigora University lecturers was carried out in Batu Kumbung village, Lingsar sub-district, West Lombok Regency, in Batu Kumbung village there are several MSMEs engaged in the culinary field such as Clarias Food, Mangosteen Coffee, Ant Sugar, Dodol, Klepon and Fresh Fruit businesses. However, these MSMEs have not been maximal in marketing the results of products made, especially digital marketing, currently product marketing is still carried out traditionally, so efforts are needed to increase the marketing of products that have been produced, to assist in digital marketing, a digital market application is needed that can be used to promote a brand using digital media that can reach consumers in a timely, personal, and relevant manner. The output achieved is the creation of a digital market application (E-Commarce Website) so that it can assist MSMEs in marketing their respective products. With this digital market application, it makes it easier for MSMEs, starting from the promotion process to the sales transaction process for MSME results in the culinary field in Batu Kumbung village.